Self-assessment of treatment targets in patients with inflammatory bowel disease using a survey - Philipp A. Reuken; Philip C. Grunert; Andreas Lügering; Niels Teich; Andreas Stallmach (Therapeutic Advances in Gastroenterology, 2020)
Background: Physicians can improve their relationships with patients by understanding and meeting patients’ treatment targets, leading to higher adherence to therapy and improved disease prognosis. In the current study, we performed a questionnaire-based survey to further understand treatment targets in patients with inflammatory bowel disease (IBD). Methods: We created a questionnaire based on a point-allocation scale with 10 treatment target items. A total of 234 patients with IBD [Crohn’s disease ( n  = 129) and ulcerative colitis ( n  = 105)] participated in three German IBD centers. Patients were asked to allocate a total of 10 points across the 10 items, with more points indicating more importance. Results: The most important treatment targets for patients regarding their therapy were quality of life (2.78 points), control of defecation (1.53 points), and avoidance of IBD-related surgery (1.69 points). Avoiding surgery for IBD was less important in patients who had already undergone a surgical procedure than in those who had not (1.26 points versus 1.89 points, p  < 0.001). Typical treatment targets, including mucosal healing (0.52 points) and normal biochemical markers (0.39 points), were not scored high by patients. The least important item was the possibility of all-oral therapy (0.19 points in 33 patients, 0 points in 201 patients). Conclusion: Treatment targets for patients were primarily related to quality of life, such as therapy side effects. Knowing these targets may improve patient–physician relationships and communication, and consequently, adherence to therapy.